2019
DOI: 10.3892/ijo.2019.4712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumor‑targeting properties of directly and indirectly radioiodinated designed ankyrin repeat protein (DARPin) G3 variants for molecular imaging of HER2

Abstract: Evaluation of human epidermal growth factor receptor 2 (HER2) expression levels in breast and gastroesophageal cancer is used for the stratification of patients for HER2-targeting therapies. The use of radionuclide molecular imaging may facilitate such evaluation in a non-invasive way. Designed ankyrin repeat proteins (DARPins) are engineered scaffold proteins with high potential as probes for radionuclide molecular imaging. DARPin G3 binds with high affinity to HER2 and may be used to visualize this important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 39 publications
5
39
0
Order By: Relevance
“…In order to prevent the accumulation of activity in these organs, we attempted to optimize the non-residualizing properties of the iodine label. In the first study, sitespecific attachment of iodo-((hydroxyphenyl)ethyl) maleimide (HPEM) label via a GGGC linker indeed decreased the activity uptake in the kidneys [8]. However, a switch of renal to hepatobiliary excretion of DARPin was observed, which was undesirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent the accumulation of activity in these organs, we attempted to optimize the non-residualizing properties of the iodine label. In the first study, sitespecific attachment of iodo-((hydroxyphenyl)ethyl) maleimide (HPEM) label via a GGGC linker indeed decreased the activity uptake in the kidneys [8]. However, a switch of renal to hepatobiliary excretion of DARPin was observed, which was undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…A new class of targeting molecules, engineered scaffold proteins (ESPs), is promising agents for tumor-targeted delivery of radionuclides [1]. Several types of ESPs, such as affibody molecules [2], ADAPTs [3], and DARPins [4][5][6][7][8][9] demonstrated efficient tumor targeting and high contrast of radionuclide imaging in preclinical studies. DARPins are built of 4-6 repeat modules of 33 amino acids and have a molecular weight of 14-18 kDa [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 125 I]I-para-iodobenzoate is only one of the potential pendant groups providing a non-residualizing radioiodine label. Alternatively, labeled iodo-hydroxyphenylethyl-maleimide (I-HPEM) [55,56] or 4-iodophenethylmaleimide (I-PEM) [57] can be used for indirect radioiodination of affibody molecules. These alternative pendant groups have different rates of excretion from normal tissues compared to PIB, which opens an opportunity for finding the most suitable variant.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ESPs can be genetically engineered to incorporate peptide-based chelators, e.g., histidine tags for labeling with technetium-99m tricarbonyl, and can generally tolerate harsh radiolabeling conditions, such as high temperature or changes in pH. A class of ESP, the designed ankyrin repeat proteins (DARPins), demonstrated excellent results for radionuclide molecular imaging of HER2 in preclinical studies, providing high tumor-to-nontumor tissue ratio shortly after injection [ 22 , 23 , 24 ]. The DARPin scaffold consists of four to six helix-turn-helix units and has molecular weight from 14 to 18 kDa, depending on the number of units.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of a radionuclide and chemistry for its conjugation to a targeting probe is essential. Experience with other targeting proteins (affibody molecules [ 26 ] and DARPins targeting HER2) [ 22 , 23 , 24 , 27 ] demonstrated that the selection of an optimal labeling approach can increase tumor-to-organ ratios by an order of magnitude. Modification of the protein surface by a radionuclide in combination with a chelator or linker for coupling results in the alteration of off-target interactions with blood vessels and normal tissues.…”
Section: Introductionmentioning
confidence: 99%